eCM 2021
DOI: 10.22203/ecm.v041a10
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyaluronic acid on nucleus pulposus extracellular matrix production through hypoxia-inducible factor-1α transcriptional activation of CD44 under hypoxia

et al.

Abstract: Intervertebral disc degeneration (IDD) is the leading cause of low-back pain. Implantation of hyaluronic acid (HA) is potentially a therapeutic strategy for IDD, but its pharmacological effects and mechanism under hypoxic conditions remain unclear. In this study, the expression of extracellular matrix genes and proteins were enhanced in nucleus pulposus cells (NPCs) in the presence of HA under hypoxic condition, as shown by real-time reverse transcription-polymerase chain reaction, immunofluorescence staining,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The membrane receptors for hyaluronan CD44 play important roles in cartilage homeostasis [ 106 , 107 ]. In fact, increasing CD44 expression has previously been correlated with matrix synthesis in NP cells of degenerating IVDs [ 108 ]. FN1 is a glycoprotein present at the cell surface and in the extracellular matrix that increases with disc degeneration [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…The membrane receptors for hyaluronan CD44 play important roles in cartilage homeostasis [ 106 , 107 ]. In fact, increasing CD44 expression has previously been correlated with matrix synthesis in NP cells of degenerating IVDs [ 108 ]. FN1 is a glycoprotein present at the cell surface and in the extracellular matrix that increases with disc degeneration [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially, hyaluronic acid-based hydrogels have been drawing increasing attention as the ideal candidates for IDD, 92 because of their potential to repair and regenerate the NP through providing a three-dimensional microenvironment for the implanted cells, 93 restoring biomechanical properties, 94 reducing inflammation response, and nociceptive behavior, 95 promoting ECM synthesis, 96 and promoting stem cell differentiation to NP-like cells. 97 Animal experiments revealed that the injection of hyaluronic acid hydrogel not only restored the height of the intervertebral disc but also reduced inflammation and promoted the synthesis of ECM.…”
Section: Hydrogel-based Biomaterialsmentioning
confidence: 99%
“…(1) Providing a three-dimensional microenvironment for the implanted cells (2) Restoring biomechanical properties; (3) Reducing inflammation response and nociceptive behavior; (4) Promoting the synthesis of ECM; (5) Promoting stem cell differentiation to NP-like cells. [92][93][94][95][96][97] Improving VAS, ODI, SF-36 scores, and disc quality quantified by Pfirrmann grading and apparent diffusion coefficient on diffusion MRI in the short and long term.…”
Section: Side Effectsmentioning
confidence: 99%
“…Nucleus pulposus tissue contain abundant ECM including collagen II (COL2) and aggrecan (ACAN) that are responsible for maintaining the mechanical load of IVD [26,27]. Over the years, many studies have shown that hy- poxia could induce various cell types to enhance COL2 and ACAN expression via HIF1α, including NPCs [10,[28][29][30][31][32]. Matrix metalloproteinases (MMPs) are endopeptidases of the ECM that have the ability to degrade almost all known components of the ECM in IVDs.…”
Section: Ecm Metabolism and Cell Phenotypementioning
confidence: 99%